O pensamento computacional como alternativa em atividades de aprendizagem por meio da resolução de problemas - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The present work presents alternatives for the insertion of Computational Thinking in Basic Education through the Problem Solving learning methodology. Currently, the teaching of mathematics is characterized by the frequent use of the traditional teaching model. This teaching methodology has great relevance in the educational context and it is one of the methodologies that are responsible for the advancement of mathematics teaching. However, it is important that alternatives are also pused in which students are encouraged to develop their creativity and begin to build concepts and act actively in their learning process instead of being characterized as a passive subject who receives information and starts repeating them. From this perspective, the use of Computational Thinking in learning through Problem Solving stands out, proposing problem situations in which the resolution methods are unknown and the students are guided by the teacher to develop their own resolution methods from relationships with other situations in which solutions are known, in addition to relying on the pillars of Computational Thinking. In this way, the student, when using concepts from computer science, becomes an active agent of their learning process. However, for these alternatives to be applied satisfactorily, it is necessary for teachers to have knowledge about the subject. From this, the present work achieved the expected objectives by presenting alternatives for the insertion of Computational Thinking through learning with the Problem Solving technique in basic education and its forms of plugged and unplugged application to the research subjects, who are undergraduates of Mathematics Course – Licentiate. From this, the present work achieved the expected objectives by presenting alternatives for the insertion of Computational Thinking through learning with the Problem Solving technique in basic education and its forms of plugged and unplugged application to the research subjects, who are undergraduates of Mathematics Course – Licentiate. In addition, there was a need to expand discussions and researches on Computational Thinking during the process of training mathematics teachers due to the insufficiently developed or mistaken understanding by a significant part of the research subjects about a topic that contributes to the full training of students and which has its development proposed by the BNCC.
Keywords: Pensamento computacional; Resolução de problemas; Computação plugada e desplugada; Educação Básica; Ensino de Matemática; Computational thinking; Problem solving; Plugged and unplugged computing; Basic education; Mathematics teaching; CNPQ::CIENCIAS EXATAS E DA TERRA